CO2 sequestration by direct gas–solid carbonation of fly ash with steam addition. (20th March 2018) - Liu, Wei; Su, Sheng; Xu, Kai; Chen, Qindong; Xu, Jun; Sun, Zhijun; Wang, Yi; Hu, Song; Wang, Xiaolong; Xue, Yanting; Xiang, Jun
Abstract: Mineral carbonation using alkaline industrial solid wastes is a promising CO2 sequestration technology. In this work, the effects of temperature, CO2 content, steam content, and reaction time on CO2 sequestration at atmospheric pressure were studied by the direct gas–solid carbonation of circulating fluid bed fly ash in a thermogravimetric analyzer and a fixed bed reactor system. Results indicate that increasing the temperature and the content of CO2 and H2 O(g) can improve the CO2 sequestration efficiency of the circulating fluid bed fly ash. However, the effect of CO2 content is not as significant as that of temperature and H2 O(g) . The maximum CO2 sequestration capacity of 60 g CO2 /kg fly ash with a maximum sequestration efficiency of 28.74% was achieved at 600 °C with 20% H2 O(g) addition. The Brunauer–Emmett–Teller surface area and the pore volume decreased with the increase in average pore size after carbonation, due to the formation of a dense carbonate protective layer and pore blockage. With steam addition, the surface area and the pore volume increase, which contributes to the conversion of CaO to CaCO3 . The production of Ca(OH)2 or transient Ca(OH)2 and the enhancement of CO2 molecular mobility account for the promotion of steam in the carbonation process. The promotion mechanism of steam in different stages of reaction and temperature were explored in detail. Given the rich reserves of fly ash in China, it shows a good application prospect to use the Chinese fly ash as a mineral carbonation feedstock, which may not only reduces CO2 emission, but also stabilizes the wastes. Highlights: The sequestration potential of circulating fluid bed fly ash under dry conditions was estimated. The process parameters and physical structure of the gas–solid carbonation process were explored. The reaction mechanism with steam addition was investigated.